The age of seeds and cold, and their The effect of absorption, and the seeds germination of Ziziphus spina christi seeds (Journal of Academic Research, 2021)
The Sidr plant is one of the important plants as it is the main source of bee pasture in Wadi Dawain, which is characterized by the production of the finest and most expensive types of honey.As a result of the deterioration of the Sidr trees as a result of logging and the erosion of torrential rains for most of the trees,The aim of the research was to find ways to increase the rate and speed of germination of Sidr seeds, especially those of old ages.. The research was conducted in the Postgraduate Studies Laboratory - College of Science - Hadramout University to study the effect of coldness frigidity on the drinking, percentage and speed of germination speed of Sidr seeds. The production of 2017 and 2018 were obtained from the Dawaan Honey Bee Center, Hadhramout, Yemen. The seeds were kept in refrigerator at 4 °C for 4 hours before and after submerged in water for 24 hours. A completely randomized design with three replications was used. The data were statistically analyzed and the means were compared to estimate the least significant difference at the 5% level of significance..The result revealed that 2018 seeds production was significantly higher compared to seeds of 2017 production in the terms of water absorption, on the other hand the best seeds treatment was frigidity followed by absorption. Treatment seeds with immersion followed by frigidity showed the lowest. It was found that pre-immersion cooling increased the rate and speed of germination of both productions.Keywords: seeds immersion, buckthorn seeds, low temperature،